'Resilience' – a characteristic clinicians now need to acquire. Issue 4 (27th July 2016) - Kirby, Roger
Abstract : Recently, the Chairman of the General Medical Council (GMC), Professor Sir Terence Stephenson, commented that each and every doctor can expect to be the subject of a complaint and investigated at some stage in his or her career by the GMC, and that rather than be downhearted about this, doctors need to develop 'resilience' in the face of criticism or an investigation…